PENGARUH KUALITAS WEBSITE TERHADAP NIAT UNTUK MEMBELI DENGAN VARIABEL INTERVENING TRUST DALAM E-COMMERCE - , Khayat Rosyadi, SE., Dr.Didi Achjari, M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this study was to provide empirical evidence of the influence of website quality toward intention to purchase with intervening variable trust in e-commerce. In this study the authors used perceived information quality, system quality and perceived service quality as the dimensions of website quality. Employing a sample of 120 respondents and processed using partial least squares (PLS) with smartPLS 2.0 softwarethe results indicate that perceived information quality, perceived system quality have a positive effect toward trust and trust significantly influence intention to purchase, but not for perceived service quality toward trust. This study indicate the importance of website quality in e-commerce success.